Biallelic Loss of Function Variant in SEC31A Is Associated With Lethal Neurodevelopmental Disorder, Dysmorphic Features, and Skeletal Defects - Almontashiri, Naif A. M.; Mushiba, Aziza; Alruqi, Haya; Alharby, Essa; Hashmi, Jamil Amjad (Clinical genetics, 2025)
Biallelic loss of function variant in SEC31A is associated with lethal neurodevelopmental disorder, dysmorphic features, and skeletal defects.Biallelic loss of function variant in SEC31A is associated with lethal neurodevelopmental disorder, dysmorphic features, and skeletal defects.